Technology, Gender and Fishing in an Odisha Village. (June 2022) - Ray, Sthitapragyan; Mukherjee, Sramana
The introduction of a new fishing technology in a small riverine village of Odisha resulted in paradoxical socio-economic outcomes. The fresh and flowing water pisciculture through the innovative Pen technology, which was based on an enclosure aquaculture system, bound from all sides by a close-knit row of multiple pens, improved productivity, income and employment levels of the fishing community. But the new technology also aggravated extant gender inequalities in the village, located on the banks of the river Mahanadi. The gendering of access to, control over and use of Pen culture in the fishing village of Naraj decided the winners and losers in this technological change. Systematic social closure and institutional bias not only ensured the exclusion of fisherwomen from accessing and utilising the new productive technology and related resources in Naraj but also reinforced the traditional male domination in the fishery sector.